Literasi Keuangan dan Kecemasan Finansial sebagai Penentu Penggunaan Fintech dan Perilaku Keuangan - Wibowo, Erwin Sya’ban Ardi; Darwin, Darwin; Faderica, Jennyfer; Kwan, Juy Celina; Wijaya, Metta Julylia; Wijaya, Philip (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2026)
Generation Z is a group that's very comfortable with digital technology and is the main group using financial technology, or fintech, services. They depend a lot on digital wallets, mobile banking, and PayLater services because these offer ease, quick access, and flexibility. However, even though they use fintech a lot, it doesn't always mean they make smart financial choices, which can lead to financial stress and poor financial decisions. This study looks at how financial knowledge affects the way Generation Z uses fintech, with financial anxiety acting as a middle factor. The research uses a quantitative method, where questionnaires were given to students who regularly use fintech services. The tools used in the study were based on established indicators of financial knowledge, financial anxiety, and fintech usage from past research. The data was analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results show that financial knowledge has a positive effect on both financial anxiety and fintech usage. Financial anxiety was also found to impact fintech usage and plays a role in how financial knowledge influences the use of fintech. These findings show that the financial behavior of young people isn't just about knowing financial things, but also about their mental state and how it affects their use of digital services. This study has important implications for creating better financial literacy programs and teaching young people how to use fintech healthily, so they can use it in a more responsible and sustainable way